ASSEMBLAGE OF WOOD PIECES AS AN EXPERIENCE OF POWER DIALOGUE IN INSTALLATION - Samuel, Awuni; Bonsu Kwame, Opoku; Eyram Emmanuel, Donkor; Panin Kwame Baah, Owusu (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The powerful presence and physicality of wood has changed over time with contemporary art practices. Woodworking techniques have evolved, which has led to the expansion of its expected limits. This change and rethinking, process, forms and materiality creates a very interesting conversation. The aim of the study employed assembling of wood off cuts by using connectivity as a technique in place of carving and other methods, generating a flexible sculptural form being able to take different display experiences. Studio-based research under qualitative research design was adopted for the study. The research instruments used were observation and photographs. This expository experience in the study was used to question the dialogue of society's experiences of power. The study displays an examination of structure, convention and circumstances of power in the dialogue form depicted in the assemblage of wood pieces as an experience.